Development of active learning management model for active citizenship competencies enhancement in elementary school - Supachai Somnual; Kittichai Suthasinobon; Rungtiwa Yamrung (Institute of Advanced Engineering and Science, 2023)
The purpose was to develop and study the effectiveness and efficiency of an active learning management model for developing active citizenship competencies for primary school students. The sample group was fifth-grade students at a demonstration school. The research instruments included: a manual for the active learning management model, active learning lesson plans, an active citizenship competencies test, and a satisfaction questionnaire. Statistics for data analysis were percentage, mean, standard deviation, and dependent sample t-test. The research results were: i) A six-step active learning management model was designed for developing active citizenship competencies for primary school students: step 1 situation to the problem, step 2 original knowledge, step 3 collaboration, step 4 information gathering, step 5 active application, and step 6 lead to reflection and assessment. A consistency assessment (item objective congruence (IOC), 5-point scale) of the model by a group of experts resulted in the highest level (mean=4.69, SD=0.47); ii) The efficacy of the active learning management model in developing active citizenship competencies were measured for knowledge, higher-order thinking skills, and attributes. For each of the measured components, the improvement in average score was statistically significant at the 0.05 level; and iii) The satisfaction of students with active learning management was high (mean=4.47, SD=0.74).